Elevated levels of CD4(+)CD25(+)FoxP3(+) T cells in systemic sclerosis patients contribute to the secretion of IL-17 and immunosuppression dysfunction. - Xinjuan Liu (Public Library of Science (PLoS), 2013)
Objective Immune imbalance between regulatory T (Treg) and Th17 cells is a characteristic of systemic sclerosis (SSc). The functional heterogeneity among Treg can be elucidated by separating Treg into different subsets based on the expression of FoxP3 and CD45RA. The aim of this study was to investigate the role of Treg subsets in the immune imbalance in naïve SSc. Methods Peripheral blood mononuclear cells (PBMCs) of 31 SSc patients and 33 healthy controls were analyzed for the expression of CD4, CD25, CD45RA, CTLA-4, FoxP3, and IL-17 using flow cytometry. Treg immunesuppression capacity was measured in co-culture experiments. The expression of FoxP3, CTLA-4, IL-17A, and RORC mRNA was measured by real-time PCR. Results The frequency of CD4(+)CD25(+)FoxP3(+) Treg cells was significantly elevated in patients with SSc (3.62±1.14 vs 1.97±0.75, p<0.001) with diminished immunosuppression capacity. In SSc, the proportion of FoxP3(high)CD45RA(-) activated Treg cells (aTreg) was decreased, the proportion of FoxP3(low)CD45RA(-) T cells was increased, and the proportion of FoxP3(low)CD45RA(+) resting Treg cells (rTreg) was decreased. The immune suppression capacity of aTreg and rTreg was diminished, while FoxP3(low)CD45RA(-) T cells exhibited a lack of suppression capacity. The immune dysfunction of aTreg was accompanied by the abnormal expression of CTLA-4. Th17 cell numbers were elevated in SSc, FoxP3(low)CD45RA(-) T cells produced IL-17, confirming their Th17 potential, which was consistent with the elevated levels of FoxP3(+)IL-17(+) cells in SSc. Conclusion A decrease in aTreg levels, along with functional deficiency, and an increase in the proportion of FoxP3(low)CD45RA(-) T cells, was the reason for the increase in dysfunctional Treg in SSc patients, potentially causing the immune imbalance between Treg and Th17 cells.